Republic of Poland : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Staff Report; Press Release; and Statement by the Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Background: Poland's strong fundamentals and sound policies helped it to successfully withstand several bouts of market turbulence and paved the way for economic recovery. While Poland has benefited from its continued transformation into a more open and dynamic economy, its substantial trade and financial linkages with global markets, combined with still-large financing needs, also make it vulnerable to external shocks. Outlook and risks: With only modest growth in its trading partners, economic activity in Poland is expected to remain moderate in the near term. Risks remain tilted to the downside amid concerns about a protracted slowdown in the euro area, continued geopolitical tensions in the region, and uncertainty surrounding normalization of monetary policy in the United States. Domestically, the risk of continued disinflation remains high. Flexible Credit Line (FCL): Against this background, the authorities are requesting a new two-year precautionary FCL arrangement with proposed lower access in the amount of SDR 15.5 billion (918 percent of quota) and cancellation of the current arrangement, approved on January 18, 2013. Poland's improved economic fundamentals and increased policy buffers have reduced financing needs. However, external risks remain elevated. In this context, the authorities consider that a new FCL in the requested amount would provide an important insurance against external risks, help sustain market confidence, and support their economic strategy. At the same time, the authorities consider that the substantial reduction in access sends a clear signal of their intention to fully exit from the FCL once external risks recede. In staff's view, Poland continues to meet the qualification criteria for access under the FCL arrangement. Fund liquidity: The impact of the proposed commitment of SDR 15.5 billion on Fund liquidity would be manageable. Process: An informal meeting to consult with the Executive Board on a possible FCL arrangement for Poland was held on December 19, 2014.